El empleo de medidas correctivas y regulatorias en el derecho del consumidor - Rodríguez García, Gustavo (Universidad ESAN, 2025)
Corrective measures are mandates aimed at repairing the legality violated by the offending party's conduct. However, the power to issue them cannot be used to fill alleged regulatory gaps or to replace legislative functions. This paper critically analyzes their treatment in consumer protection cases and explains why a distinction should be made between genuine corrective measures and regulatory measures that appear to be so. It also examines the risks of public administration misuse of this tool, which compromises the legal security of those governed, distorts competition, and weakens trust in the authorities

Corrective measures are mandates aimed at repairing the legality violated by the offending party's conduct. However, the power to issue them cannot be used to fill alleged regulatory gaps or to replace legislative functions. This paper critically analyzes their treatment in consumer protection cases and explains why a distinction should be made between genuine corrective measures and regulatory measures that appear to be so. It also examines the risks of public administration misuse of this tool, which compromises the legal security of those governed, distorts competition, and weakens trust in the authorities.
Keywords: Corrective measures; Consumer protection; Administrative law; Sanctioning power; Hidden regulation; Medidas correctivas; Protección al consumidor; Derecho administrativo; Potestad sancionadora; Regulación encubierta; https://purl.org/pe-repo/ocde/ford#5.05.01